Triclabendazole resistance in Fasciola hepatica: First report in sheep from the Santa Cruz province, Argentinian Patagonia - Larroza, Marcela Patricia; Aguilar, Marcelo Javier; Soler, Paula; Mora, Julio Cesar; Roa, Martin Angel; Cabrera, Francisco Ra; Martinez Stanziola, Juan Pablo; Ceballos, Laura; Alvarez, Luis (Elsevier, 2023)
In the fall of 2022, decreased triclabendazole (TCBZ) efficacy against F. hepatica was suspected in a sheep farm located in the Santa Cruz province, Argentinian Patagonia. Since TCBZ-resistance in F. hepatica has never been reported in this province, this study aimed to confirm potential TCBZ-resistance in F. hepatica and to evaluate the efficacy of closantel (CLO) and nitroxinil (NTX), through faecal egg count reduction test (FECRT), and the efficacy of albendazole (ABZ) through the in vitro egg hatch test (EHT) in sheep. Sixty-eight (68) animals were selected from a herd of eighty (80) female Merino naturally infected with F. hepatica based on eggs per gram of F. hepatica (EPGFh) counts and assigned into four (4) groups (n = 17 per group): Group Control, animals did not receive anthelmintic treatment; Group TCBZ, animals were orally treated with TCBZ (12 mg/kg); Group CLO, animals were orally treated with CLO (10 mg/kg); and Group NTX, animals were subcutaneously treated with NTX (10 mg/kg). The fluke egg output was monitored on days 0 and 21 post-treatment. For the EHT, liver fluke eggs were isolated from faecal samples (approx. 50 g) collected from animals of the control group. TCBZ efficacy against liver fluke was 53.4%, confirming the presence of TCBZ-resistant isolates on the farm. CLO and NTX were highly effective (100%) for the treatment of F. hepatica on this farm. The EHT was carried out in two different laboratories, in which was observed an ABZ efficacy of 95.8 (Bariloche) and 96.5% (Tandil). These results indicate the ABZ susceptibility of this F. hepatica isolate and the inter-laboratory precision of the test.